Numerical investigation of aerodynamics of a helicopter articulated main rotor in hovering and horizontal flight - Abalakin, I.; Bobkov, V.; Kozubskaya, T.; Tsvetkova, V.; Vershkov, V.; Kritsky, B.; Mirgazov, R. (My University, 2021)
The paper is devoted to the numerical study of aerodynamic characteristics of a four-bladed articulated main rotor of a helicopter with cyclic pitch control and flapping motions of the blades and to the comparative analysis of the results against the similar case of rigid rotor with the fixed pitch angle and precone angle. The numerical investigation is carried out for the following working conditions: hover mode without cyclic control; forward flight without cyclic control; forward flight with cyclic control. The computations are performed on unstructured hybrid meshes using the in-house CFD code NOISEtte.